2020
DOI: 10.1515/med-2020-0043
|View full text |Cite
|
Sign up to set email alerts
|

Body composition indices and cardiovascular risk in type 2 diabetes. CV biomarkers are not related to body composition

Abstract: AbstractBackgroundThis study aims to explore the correlations of body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), waist-to-hip ratio (WHR) and body composition with levels of asymmetric dimethylarginine (ADMA), endothelin 1(ET-1), N-terminal brain natriuretic pro-peptide (NT-proBNP) and calculated cardiovascular risks. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…45 BMI is the obesity index that, more than others, is related to the estimated risks for coronary heart disease and stroke in the T2D population based on specific cardiovascular risk calculators, such as the Framingham Risk Score, the UKPDS version 2.0 and the ADVANCE risk engines. 46 Interestingly, we observed an improvement in BMI or a stabilization of the parameters when participants were engaged with web-based intervention, thus confirming the potential of this approach.…”
Section: Discussionsupporting
confidence: 73%
“…45 BMI is the obesity index that, more than others, is related to the estimated risks for coronary heart disease and stroke in the T2D population based on specific cardiovascular risk calculators, such as the Framingham Risk Score, the UKPDS version 2.0 and the ADVANCE risk engines. 46 Interestingly, we observed an improvement in BMI or a stabilization of the parameters when participants were engaged with web-based intervention, thus confirming the potential of this approach.…”
Section: Discussionsupporting
confidence: 73%
“…[35] Few studies in the literature have attempted to correlate the use of biomarkers, especially those analyzed in the present study, and the CVR predicted by scores in the diabetic population. [36][37][38][39][40][41] One of these studies evaluated the association between a set of biomarkers that analyze different metabolic pathways, such as Asymmetric dimethylarginine (ADMA), Soluble endothelin-1 (ET-1), Placental growth factor-1 (PIGF-1) and NT-pro-BNP and the CVR predicted by the UKPDS and Action in Diabetes and Vascular disease (ADVANCE) scores in diabetic patients. This study showed that ADMA and PIGF-1 were not associated with CVR strati cation with any of the scores, while ET-1 was associated with the risk of stroke by the UKPDS and NT-proBNP was associated with CVR predicted by both tools.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 34 papers were found unsuitable after full-text review for the following reasons: 20 studies were in the general population, not in people with diabetes (population not as per protocol); in eight studies, subgroup analysis of people with diabetes was not available; three studies had an improper selection of intervention and control group as per protocol; and three studies assessed non-CV outcomes (outcomes not as per the protocol). Finally, 11 papers met the inclusion criteria and were included in the systematic review [12][13][14][15][16][17][18][19][20][21][22]. *Reasons for exclusion: 20 studies were in the general population, not in people with diabetes; in eight studies, subgroup analysis of people with diabetes was not available; three studies had an improper selection of intervention and control group as per protocol; and three studies assessed non-CV outcomes (outcomes not as per the protocol).…”
Section: Reviewmentioning
confidence: 99%
“…ADMA, endothelin 1 (ET-1), and NT-proBNP, as well as body composition parameters (BF%, FM, FFM, and TBW), were investigated in a study by Markova A et al [13] to see if they were associated with calculated CV risks. It was discovered that the strongest correlations between the calculated CV risk estimations were found with BMI, WHtR, and BF%.…”
Section: Interpretation Of Included Studiesmentioning
confidence: 99%